Sociodemographic inequalities in vegetables, fruits, and animal source foods consumption in children aged 6–23 months from 91 LMIC - Ricardo, Luiza I. C.; Gatica-Domínguez, Giovanna; Neves, Paulo A. R.; Vaz, Juliana dos Santos; Barros, Aluisio J. D.; Wehrmeister, Fernando C. (Frontiers in Nutrition, 2023)
No multi-country analysis described patterns and inequalities for the brand-new feeding indicators proposed by WHO/UNICEF: zero consumption of vegetables and fruits (ZVF) and consumption of eggs and/or flesh (EFF). Our aim was to describe patterns in the prevalence and social inequalities of ZVF and EFF among children aged 6-23 months in low- and middle-income countries. Data from nationally representative surveys (2010–2019) in 91 low- and middle-income countries were used to investigate within-country disparities in ZVF and EFF by place of residence, wealth quintiles, child sex and child age. The slope index of inequality was used to assess socioeconomic inequalities. Analyses were also pooled by World Bank income groups. The prevalence of ZVF was 44.8% and it was lowest in children from upper-middle income countries, from urban areas, and those 18-23 months. The slope index of inequality showed that socioeconomic inequalities in the prevalence of ZVF were higher among poor children in comparison to richest children (mean SII = -15.3; 95%CI: -18.5; -12.1). Overall, 42.1% of children consumed egg and/or flesh foods. Being a favorable indicator, findings for EFF were generally in the opposite direction than for ZVF. The prevalence was highest in children from upper-middle income countries, from urban areas, and those 18-23 months of age. The slope index of inequality showed pro-rich patterns in most countries (mean SII = 15.4; 95%CI: 12.2; 18.6). Our findings demonstrate that inequalities exist in terms of household wealth, place of residence, and age of the child in the prevalence of the new complementary feeding indicators. Moreover, children from low- and lower-middle countries had the lowest consumption of fruits, vegetables, eggs, and flesh foods. Such findings provide new insights towards effective approaches to tackle the malnutrition burden through optimal feeding practices.